Systematic reviews and meta-analyses of human and animal evidence of prenatal diethylhexyl phthalate exposure and changes in male anogenital distance. (19th May 2018) - Dorman, David C.; Chiu, Weihsueh; Hales, Barbara F.; Hauser, Russ; Johnson, Kamin J.; Mantus, Ellen; Martel, Susan; Robinson, Karen A.; Rooney, Andrew A.; Rudel, Ruthann; Sathyanarayana, Sheela; Schantz, Susan L.; et al.
ABSTRACT: Male reproductive alterations found in animals and humans following in utero phthalate exposure include decreased anogenital distance (AGD) and other reproductive-tract malformations. The aim of this investigation was to conduct systematic reviews of human and animal evidence of the effect of in utero exposure to diethylhexyl phthalate (DEHP) on anogenital distance (AGD) in males. PubMed, Embase, and Toxline were searched for relevant human and experimental animal studies on August 15, 2016. Search results were screened for relevance, and studies that met the inclusion criteria were evaluated for quality and data extracted for analysis. Confidence in the human and animal bodies of evidence was assessed and hazard conclusions reached by integrating evidence streams. The search yielded 6 relevant human studies and 19 animal studies. Meta-analysis of 5 human observational prospective cohort studies showed that increased maternal urinary concentrations of DEHP metabolites were associated with decreased AGD in boys (−4.07 [CI, −6.49 to −1.66] % decrease per log10 rise in DEHP metabolites). Meta-analysis and meta-regression of the 19 experimental animal studies found reduced AGD with DEHP treatment, with a dose-response gradient, and with heterogeneity explained by species and strain. There is a moderate level of evidence from human investigations and a high level of data from animal studies that in utero exposure to DEHP decreases AGD. Based upon the available human and animal evidence, and consideration of mechanistic data, DEHP is presumed to be a reproductive hazard to humans on the basis of effects on AGD.